Experimental Study of the Effect of Magnetization on Bioethanol Injectors on Spray Characteristics for Applications in the SINJAI-150 Engine - Amalia Dwi Utami; Bambang Sudarmanta; Budi Utomo Kukuh Widodo; Ary Bachtiar Krisna Putra; Is Bunyamin Suryo (LPPM, Institut Teknologi Sepuluh Nopember, Indonesia, 2019)
In general, the hydrocarbon molecules in the fuel perform vibrational activity towards the core and attract each other, forming clustering molecules. Induction of a magnetic field in the fuel flow can change the hydrocarbon molecules so that their arrangement becomes more regular (de-clustering). The induction of the magnetic field in this research utilized a coil that was fed by an output current from the SINJAI-150 engine alternator. Magnetic field placement was placed before Bioethanol E100 fuel entered the injector. Observation of the magnetization of the fuel was carried out molecularly with the FTIR (Fourier Transform-Infra Red Spectroscopy) test and observing the characteristics of the fuel spray at the injector output. The results obtained were an increase in the fuel transmittance of Bioethanol E100 up to 41.31% for C-H compounds, 48.8% for C-O compounds, and 114% for O-H compounds compared to standard conditions. In the spray characteristics, there was an increase in the spray angle up to 2 and a decrease in the Sauter Mean Diameter (SMD) to 1.312 mm, due to a decrease in the value of the fuel properties in the form of surface tension, viscosity, and density up to 2.6%, 10.28% and 10.15% from the standard state without magnetization. As a result of decreasing the density value, the mass flow rate of the fuel decreases to 10.28% from the standard conditions at 2,000 rpm.